PERAN FOOD AND AGRICULTURE ORGANZATION (FAO) DALAM MENGATASI KRISIS PANGAN DI BANGLADESH TAHUN 2007-2012 - Nasution, Ade Irma Suriana; Jamaan, Ahmad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This research aims to look at the role of the Food and Agriculture Organization (FAO) in overcoming the food crisis in Bangladesh. The food crisis means losing access to food for the majority of the world community or lack of resources used to produce food. In Bangladesh there are several causes of the food crisis include natural disasters, food price inflation, the increase in population, the transfer of agricultural land, and poverty. The global food crisis provides a parallel effect on food security in Bangladesh which led to the high prevalence of malnutrition among children and women, as well as add to the high level of poverty in Bangladesh. In addressing the food crisis in Bangladesh FAO as an organization engaged in the food sector provide financial assistance and make some programs to address these issues and to supervise the program has been implemented. This research shows that the FAO managed to overcome the food crisis in Bangladesh and able to perform their functions. The success achieved in the form of: increasing the availability of food, rising incomes of the poor and the initiative when confronted again with the food crisis in the future.Key word: Bangladesh, Food and Agriculture Organization (FAO), food crisis, roles.